La investigacion de frijol en campos de agricultores en el CIPA La Libertad, Peru - Sánchez N., J. (International Center for Tropical Agriculture, 1987)
Results of 2 on-farm trials carried out in Peru during 1986 are presented in table form. In 1 of the trials, drought-tolerant bean var. were evaluated with 1 and 2 irrigation treatments. In the other trial, potentially rust- tolerant var. were evaluated at 2 plant densities. For drought conditions, promising var. were Paijan 33 and Garbancillo (av. yields of 1497 and 1509 kg/ha, resp.); for rust, the most resistant was Paijan 33. (CIAT)